Contribution of taste and service quality: Case study of consumer satisfaction at Mas Imron Restaurant, Tabongo District - Rindy Riyani Bilondatu; Herlina Rasjid; Tineke Wolok (Universitas Nusa Cendana, 2026)
This study reveals that both the quality of service and the taste of the meal play crucial roles in shaping customer satisfaction at Mas Imron Restaurant. When the service provided is efficient, friendly, and attentive, customers tend to feel more valued and comfortable, which positively impacts their general experience. Equally important is the flavor and presentation of the dishes; delicious, well-prepared meals encourage diners to return and recommend the restaurant to others. The findings emphasize that consistently maintaining high culinary standards and delivering exceptional service are essential strategies for building customer loyalty. Satisfied customers are more likely to become repeat patrons, fostering long-term relationships that benefit the restaurant’s reputation and growth. Furthermore, these factors give Mas Imron Restaurant a competitive edge in a crowded meal industry by differentiating it from competitors who might not prioritize quality and service as highly. The study underscores the need for continuous quality improvement in both kitchen operations and customer service practices to sustain high levels of satisfaction. Ultimately, the combined focus on excellent taste and outstanding service not only enhances customer experiences but also contributes significantly to the restaurant’s success and reputation in a competitive market. This insight underscores the importance of a holistic approach to service and culinary excellence for long-term business growth. Keywords: Customer Satisfaction; Service Quality; Taste